Dimer models and integrable systems - Eager, Richard; Franco, Sebastian (Journal of high energy physics, 2012)
We explore various aspects of the correspondence between dimer models and integrable systems recently introduced by Goncharov and Kenyon.
Gesehen am 22.03.2018